Exploring the underlying mechanisms behind poor faecal integrity in yellowtail kingfish (Seriola lalandi): The role of dietary starch level and amylase supplementation - Peter Horstmann Zuther; Roel M. Maas; Tijmen Blok; Jeroen Kals; Marit A.J. Nederlof; Satya Prakash; Henk A. Schols; Thomas W.O. Staessen; Yaqing Zhang; Fotini Kokou; Johan W. Schrama (Aquaculture Reports)
This study explored potential underlying mechanisms (e.g. chyme characteristics, fermentation, and intestinal morphology), that contribute to the negative effect of high dietary starch on faecal integrity in yellowtail kingfish (Seriola lalandi) (experiment 1), and whether amylase supplementation can mitigate the apparent negative effects (experiment 2). Fish were fed LS (4 % starch) or HS (19 % starch) diets in experiment 1. Experiment 2 tested 21 % starch diets without amylase (NA diet) and with amylase supplementation (AS diet). Both experiments examined faeces waste production, faeces characteristics (e.g. removal efficiency and particle size distribution), distal intestine chyme composition, viscosity, osmolality, dry matter, fermentation processes (volatile fatty acids and lactic acid), and intestinal morphology. In experiment 1, the HS diet increased faecal waste production and decreased the faecal integrity. Only minor differences were observed in regard to chyme characteristics and fermentation products. Intestinal morphology appeared unaffected by the treatments. In experiment 2, the AS diet reduced faecal waste production and numerically increased removal efficiency, reducing non-removed feces compared to the NA diet. Amylase supplementation did not affect intestinal morphology or chyme characteristics. The present study showed that high dietary starch inclusion does not affect chyme dry matter content, osmolality at egestion, fermentation processes, or intestinal morphology. The exact mechanism by which high dietary starch harms yellowtail kingfish feces is unknown. The apparent negative effects on faeces may be due to variations in starch content. Amylase supplementation reduced faecal waste, partially mitigating the negative effects of high dietary starch inclusion on waste management in yellowtail kingfish.